2002
DOI: 10.1128/iai.70.2.749-761.2002
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Pro- and Anti-Inflammatory Cytokines Differentially Regulate an In Vivo Humoral Response toStreptococcus pneumoniae

Abstract: ؊/؊ mice. In this regard, a marked enhancement in the induction of proinflammatory cytokines was observed in the absence of IL-10, relative to controls. Ig isotype titers specific for the phosphorycholine determinant of C-polysaccharide were similarly regulated, but to a much more modest degree. These data suggest that proinflammatory and anti-inflammatory cytokines differentially regulate an in vivo protein-and polysaccharide-specific Ig response to an extracellular bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
76
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 85 publications
7
76
2
Order By: Relevance
“…In the absence of adjuvant, IL-6 KO mice secreted a reduced amount of NP-specific Abs compared with the WT mice (Fig. 2E, white histograms), in agreement with previous reports (31). However, oligomycin coinjection with NP-KLH elicited a strong increase in Ab titers in both WT and IL-6 KO mice, suggesting an IL-6-independent mechanism for the humoral responses induced by oligomycin.…”
Section: Oligomycin Increases Humoral Responses Independently Of Nlrpsupporting
confidence: 80%
“…In the absence of adjuvant, IL-6 KO mice secreted a reduced amount of NP-specific Abs compared with the WT mice (Fig. 2E, white histograms), in agreement with previous reports (31). However, oligomycin coinjection with NP-KLH elicited a strong increase in Ab titers in both WT and IL-6 KO mice, suggesting an IL-6-independent mechanism for the humoral responses induced by oligomycin.…”
Section: Oligomycin Increases Humoral Responses Independently Of Nlrpsupporting
confidence: 80%
“…Antibody titers against pneumococcal proteins were increased compared with those in wild-type mice. 41 Although no association was observed between the IL10 polymorphism and specific antibody levels in our population, one might expect a similar effect. Possibly, the concentration of IL-10 in low producers is sufficient to preclude finding differences in antibody titers.…”
Section: Discussionmentioning
confidence: 63%
“…We also observed an increment in total anti-PspA IgG in IL-4 KO mice immunized with either rPspA3NS or pSec-pspA3NS compared to WT animals. Higher antibody responses to PspA have previously been observed in IL-4 KO mice than in WT mice, and this is assumed to be due to the lack of suppression of the IgG response by IL-4 (14). In our present studies, we also analyzed the IgG1/IgG2a ratio, and only WT mice immunized with recombinant protein showed a marked predominance of IgG1 (IgG1/IgG2a ratio ϭ 1,024), while balanced IgG1/IgG2a ratios were observed for the other groups (ratio of 4 for pSecpspA3NS-immunized WT mice, 2 for rPspA3NS-immunized IL-4 KO mice, and 0.1 for pSec-pspA3NS-immunized IL-4 KO mice).…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-12 (IL-12) deficiency has also been correlated with increased susceptibility to pneumococcal infections, presumably due to a deficient T-cell response (10). In mice, the development of disease and the host response to the pneumococcal challenge have been studied with different strains of wild-type (WT) and knockout (KO) animals (13,14,18,25,27), but all of these studies were performed with nonimmunized mice only and reported that resolution of infection in the naïve host is mediated primarily through phagocytosis and intracellular killing by neutrophils and macrophages, which are recruited to the site of infection in response to proinflammatory cytokine and interleukin release by T lymphocytes. In accordance with this, it has been suggested that gamma interferon (IFN-␥) and tumor necrosis factor alpha (TNF-␣) produced by NK and T cells have a crucial involvement not only in the natural host defense but also in acquired resistance against S. pneumoniae (12,24).…”
mentioning
confidence: 99%